Upaya Meningkatkan Kreativitas dan Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Menengah Pertama melalui Model Pembelajaran Treffinger - Isnaini Isnaini; M. Duskri; Said Munzir (Didaktik Matematika, 2016)
Students are often confronted with problems related to mathematics in their daily life. Problem solving is one of the competencies that are the focus of mathematics learning. Solving the problem needs creativity in order to develop the imagination of the students to avoid a single answer and uniforms to students. Creativity is a process to produce something new that can be accepted as useful and defensible. The research objective of this experiment was to determine: (1) the effect of Treffinger learning model to increase of mathematical creative thinking abilities of students at SMPN 16 Banda Aceh, (2) the effect of Treffinger learning model to increase of mathematical problem solving abilities of students at SMPN 16 Banda Aceh, and (3) the description of students' response to Treffinger learning model in mathematics. The population in this study was all students of class VII SMP 16 Banda Aceh and the subject of research was selected as the experimental class was VII2. The instrument of this research was to test the ability of creative thinking and problem solving skills have the form mathematical problems of three questions, have the reliability of 0.592. The results show that: (1) there was an effect of Treffinger learning model to increase of mathematical creative thinking abilities of students at SMPN 16 Banda Aceh, (2) there was an effect of Treffinger learning model to increase of mathematical problem solving abilities of students at SMPN 16 Banda Aceh, and (3) the students of class VII-2 SMP Negeri 16 Banda Aceh have responded positively to the Treffinger learning model